GE_GERICHTE C/24381/2010 vom 13. November 2015 - GE Cour de justice (2015)
OBLIGATION D'ENTRETIEN; ENFANT; MAJORITÉ(ÂGE); DIVORCE; AUDITION DE L'ENFANT; CURATEUR; INDEMNITÉ(EN GÉNÉRAL) | CPC.298; CPC.299.1; CPC.95.2.e; CC.276; CC.285